K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 1 2017

x=3

y=4

hoac

x=9

y=-4

tk cho minh nha

24 tháng 1 2017

bạn giải chi tiết ra đi

13 tháng 10 2017

2/a/ \(x\left(x+1\right)^2\)

b/ \(\left(y+x\right)\left(y-1\right)\)

c/ \(\left(x+1\right)\left(3x-10\right)\)

d/ \(-3\left(2z+x-y\right)\left(2z+y-x\right)\)

27 tháng 7 2019

21(x-y)2-7(y-x)3 

=21(x2-y2)-7(y2-x2)

=21x2-21y2-7y2+7x2

=28x2-28y2

=28(x2-y2)

9 tháng 8 2015

a) = x^2 - y^2 - x - y

   = ( x-  y)(x + y) - ( x+ y)

  = ( x+  y)( x- y - 1 )

 

9 tháng 8 2015

a)x2-x-y2-y

=x2-y2-x-y

=(x-y)(x+y)-(x+y)

=(x+y)(x-y-1)

 

 

4 tháng 11 2021

a) \(x-xy+y-y^2=x\left(1-y\right)+y\left(1-y\right)=\left(x+y\right)\left(1-y\right)\)

b) \(x^2-2x-y^2+1=\left(x^2-2x+1\right)-y^2=\left(x-1\right)^2-y^2=\left(x-y-1\right)\left(x+y-1\right)\)

c) \(4x^2-4xy+y^2=\left(2x\right)^2-2.2x.y+y^2=\left(2x-y\right)^2\)

d) \(9x^3-9x^2y-4x+4y=9x^2\left(x-y\right)-4\left(x-y\right)=\left(9x^2-4\right)\left(x-y\right)=\left(3x-2\right)\left(3x+2\right)\left(x-y\right)\)

e) \(x^3+2+3\left(x^3-2\right)=x^3+2+3x^3-6=4x^3-4=4\left(x^3-1\right)=4\left(x-1\right)\left(x^2+x+1\right)\)

14 tháng 10 2020

6) \(9x^3y^2+3x^2y^2=3x^2y^2\left(3x+1\right)\)

7) \(x^3+2x^2+3x=x\left(x^2+2x+3\right)\)

8) \(6x^2y+4xy^2+2xy=2xy\left(3x+2y+1\right)\)

9) \(5x^2\left(x-2y\right)-15x\left(x-2y\right)=5x\left(x-2y\right)\left(x-3\right)\)

10) \(3\left(x-y\right)-5x\left(y-x\right)=\left(x-y\right)\left(3+5x\right)\)

14 tháng 10 2020

6) 9x3y2 + 3x2y2 = 3x2y2( 3x + 1 )

7) x3 + 2x2 + 3x = x( x2 + 2x + 3 )

8) 6x2y + 4xy2 + 2xy = 2xy( 3x + 2y + 1 )

9) 5x2( x - 2y ) - 15x( x - 2y ) = 5x( x - 2y )( x - 3 )

10 3( x - y ) - 5x( y - x ) = 3( x - y ) + 5x( x - y ) = ( x - y )( 3 + 5x )

4 tháng 10 2020

a) \(7x\left(y-4\right)^2-\left(4-y\right)^3\)

\(=7x\left(y-4\right)^2+\left(y-4\right)^3\)

\(=\left(y-4\right)^2\left(7x+y-4\right)\)

b) \(3x\left(x+7\right)^2-11x^2\left(x+7\right)+9\left(x+7\right)\)

\(=\left(x+7\right)\left[3x\left(x+7\right)-11x^2+9\right]\)

\(=\left(x+7\right)\left(-8x^2+21x+9\right)\)

\(=\left(x+7\right)\left(3-x\right)\left(8x+3\right)\)